Activation of macrophage TBK1‐HIF‐1α‐mediated IL‐17/IL‐10 signaling by hyperglycemia aggravates the complexity of coronary atherosclerosis: An in vivo and in vitro study. Issue 5 (28th April 2021) - Li, Qinxue; Liu, Yayun; Xia, Xin; Sun, Haichen; Gao, Jinhuan; Ren, Quanxin; Zhou, Tian; Ma, Chang; Xia, Jinggang; Yin, Chunlin
Abstract: Our purpose was to study the effect of hyperglycemia on macrophage TBK1‐HIF‐1α‐mediated IL‐17/IL‐10 signaling and its correlation with coronary atherosclerosis. A total of 135 patients with coronary heart disease (CHD) were divided into a stable CHD (SCHD) group (n = 30) and an acute myocardial infarction (AMI) group (n = 105) [nondiabetes mellitus (non‐DM)‐AMI, n = 60; DM‐AMI, n = 45] from January to September 2020. The SYNTAX score and metabolic and inflammatory markers were quantified and compared. THP‐1 cell studies and an animal study of coronary intimal hyperplasia were also carried out. We found that the DM‐AMI group showed a higher SYNTAX score than the non‐DM‐AMI group ( P < .05 ). The DM‐AMI group showed the highest expression levels of TANK‐binding kinase 1 (TBK1), hypoxia‐inducible factor 1α (HIF‐1α), and interleukin (IL)‐17 and the lowest expression level of IL‐10, followed by the non‐DM‐AMI group and the SCHD group ( P < .05) . THP‐1 cell studies showed that BAY87‐2243 (a HIF‐1α inhibitor) reversed the increase in IL‐17 and decrease in IL‐10 expression induced by hyperglycemia. Amlexanox (a TBK1 inhibitor) reversed the increase in HIF‐1α expression induced by hyperglycemia. Amlexanox treatment resulted in lower coronary artery intimal hyperplasia and a larger lumen area in a diabetic swine model. We conclude that hyperglycemia might aggravate the complexity of coronary atherosclerosis through activation of TBK1‐HIF‐1α‐mediated IL‐17/IL‐10 signaling. Thus, TBK1 may be a novel drug therapy target for CHD complicated with DM.